Development of an updated loop-mediated isothermal amplification (LAMP) assay for the rapid detection of Ralstonia syzygii subsp. celebesensis (Rsc), the causative agent of banana blood disease - Kaennuea, Thipsukon; Thanyasiriwat, Thanwanit; Rattanapolsan, Ladawan; Ponpang-nga, Pancheewan; Sangdee, Aphidech; Kawicha, Praphat (Archives of Biological Sciences, 2025)
Paper description: Banana blood disease (BBD) caused by Ralstonia syzygii celebesensis (Rsc) threatens banana production in Southeast Asia. A Loop-Mediated Isothermal Amplification (LAMP) assay was developed using a unique DNA sequence from repetitive sequence-based (rep)-PCR and tested on bacterial cultures, Rsc-spiked banana suckers and field samples. The LAMP assay matched PCR in specificity but demonstrated higher sensitivity for detecting Rsc. This rapid, field-deployable tool supports early BBD detection for improved management and reduced economic losses. Abstract: Efficient and accurate detection of Ralstonia syzygii subsp. celebesensis (Rsc), the pathogen responsible for banana blood disease, is vital for controlling its detrimental effects on banana cultivation. This study developed and assessed a loop-mediated isothermal amplification (LAMP), which detected as few as 10 cells per reaction, significantly surpassing conventional PCR, which required a minimum of 10³ cells per reaction. The LAMP assay utilizes real-time fluorescence-based Ct values and Tm analysis, ensuring reliable detection by confirming target specificity. The assay effectively identified Rsc in Rsc-spiked banana sucker samples and naturally infected field specimens using a simple, purification-free boiling DNA extraction method, making it highly adaptable for field diagnostics. By integrating real-time fluorescence detection with Tm validation, this study presents an advanced, field-deployable molecular diagnostic tool with superior sensitivity and specificity, addressing critical limitations of existing Rsc detection methods and enhancing early disease surveillance in banana cultivation.